Effect of Single Slat and Double Slat on Aerodynamic Performance of NACA 4415 - Julian, James; Iskandar, Waridho; Wahyuni, Fitri; Armansyah; Ferdyanto (International Journal of Marine Engineering Innovation and Research, 2025)
This study uses a Computational Fluid Dynamics (CFD) approach. The main object in this study is NACA 4415 with slat variations. The airfoil used as the slat is Eppler 421. Reynolds number in this study is 3Í106. This study uses an unstructured mesh with a triangular cell shape with 137824 elements. The use of slats can improve the aerodynamic performance of NACA 4415. NACA 4415 without slat stalled at AoA=16º. Stall on airfoils with a single slat and double slat occurred at AoA=20º. Slat can increase Cl in NACA 4415; however, the difference in Cl increase is not much different when using a single slat or double slat. An airfoil with a single slat, on average, can increase Cl by 20.9129%. The average increase in Cl for an airfoil with a double slat is 25.6878%. Single slat and double slat increase Cd. A single slat increased Cd with an average increase of 26.1109%, and the average increase in Cd for airfoils with double slat was 54.6152%. Single slat can produce a better Cl to Cd ratio than double slat, but the optimum AoA of double slat is 1º higher than single slat. Visualization of fluid flow at AoA=16° shows the fluid flow separation in the airfoil without a slat. The fluid flow separation can be handled well when NACA 4415 is given a single slat or double slat.